Face detection approach for video surveillance - Ting, S.C (Universiti Malaysia Sarawak, UNIMAS, 2010)
Nowadays, computer has been acts an important role in our human life. Computer has been used for purposes such as television streaming, business confidential information storage, home security monitoring, home appliances controlling and etc. All of these usages are mainly based on the computer. Hence, our computer security system has makes an important roles in preventing unauthorized access to the computer. Thus, a real time face recognition system is proposed. In this report, a real time face detection and recognition system is presented. Basically, this system applied skin colour detection to allocate the face. The system allocates the face through skin colour sensing a nd further focused image processing on the specific area in the image. The system converted the facial information to grayscale image and performing face recognition using neural network. Neural network is used for storing the facial information of the training images. The Radial Basis Function Network is used for the particular purposes. The system is able to detect and recognize the face trained. The system would show the matching percentage of target with the training images. The system can perform well in recognizing the target faces with variation of poses and facial expression with at least 60% matched the target. The system proposed a direct webcam video input in real time based for the real time face recognition system